Analisis Pengaruh Citra Destinasi, Kualitas Perjalanan Terhadap Minat Berprilaku Wisatawan Di Kepulauan Seribu Dki Jakarta Sebagai Destinasi Prioritas Indonesia - Gantina, Devita; Lintangkawuryan, Yulia (Jurnal Ilmiah Pariwisata; Vol 23 No 3 (2018): Jurnal Ilmiah Pariwisata, 2018)
The development of tourism is increasingly interesting to study, given that many domestic and foreign tourists travel. Plus, the tourism sector is being promoted by the government. In 2016 the government established 10 priority tourism destinations as "new Bali" one of which is the Thousand Islands located in DKI Jakarta. This study provides an overview of how destination images can provide self-confidence, how the quality of the trip that tourists feel and the desire of tourists to visit again or not after visiting these destinations. This research is very important to do to see whether visiting tourists will visit again in the future. This study uses descriptive quantitative methods, carried out in cross-sectional, data collection techniques by distributing questionnaires. Respondents were tourists visiting the Thousand Islands. Sampling using the Clustersamplin method. Data analysis methods are validity and reliability test, descriptive statistical analysis, Pearson correlation, and simple linear regression, using the help of SPSS 21 for window software (Pramesti, 2013: 37–66).